Hydrogen Sulfide Is a Novel Regulator of Bone Formation Implicated in the Bone Loss Induced by Estrogen Deficiency. (23rd December 2015) - Grassi, Francesco; Tyagi, Abdul Malik; Calvert, John W; Gambari, Laura; Walker, Lindsey D; Yu, Mingcan; Robinson, Jerid; Li, Jau‐Yi; Lisignoli, Gina; Vaccaro, Chiara; Adams, Jonathan; Pacifici, Roberto
ABSTRACT: Hydrogen sulfide (H2 S) is a gasotransmitter known to regulate bone formation and bone mass in unperturbed mice. However, it is presently unknown whether H2 S plays a role in pathologic bone loss. Here we show that ovariectomy (ovx), a model of postmenopausal bone loss, decreases serum H2 S levels and the bone marrow (BM) levels of two key H2 S‐generating enzymes, cystathione β‐synthase (CBS) and cystathione γ‐lyase (CSE). Treatment with the H2 S‐donor GYY4137 (GYY) normalizes serum H2 S in ovx mice, increases bone formation, and completely prevents the loss of trabecular bone induced by ovx. Mechanistic studies revealed that GYY increases murine osteoblastogenesis by activating Wnt signaling through increased production of the Wnt ligands Wnt16, Wnt2b, Wnt6, and Wnt10b in the BM. Moreover, in vitro treatment with 17β‐estradiol upregulates the expression of CBS and CSE in human BM stromal cells (hSCs), whereas an H2 S‐releasing drug induces osteogenic differentiation of hSCs. In summary, regulation of H2 S levels is a novel mechanism by which estrogen stimulates osteoblastogenesis and bone formation in mice and human cells. Blunted production of H2 S contributes to ovx‐induced bone loss in mice by limiting the compensatory increase in bone formation elicited by ovx. Restoration of H2 S levels is a potential novel therapeutic approach for postmenopausal osteoporosis. © 2015 American Society for Bone and Mineral Research.